GGBS BASED GEOPOLYMER CONCRETE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In an attempt to improve the sustainability of construction and reduce portland cement, the use of supplementary cementitious materials, such as ground granulated blast-furnace slag (GGBS), has become a common practice. Concrete is one of the most widely used construction materials which are usually associated with Portland cement as the main ingredient for making concrete. The global warming is caused by the emission of greenhouse gases such as CO2 into the atmosphere by human activities. Among the greenhouse gases, CO2 contributes about 65% of global warming.A geopolymer or alkali-activated cement is an inorganic, alumino-silicate based material. The strengths of geopolymer mortar and concrete are of the same order as those made with normal Portland cement. A wide range of materials is being used for Geopolymerization including materials rich in Si(e.g. fly ash, GGBS and rice husk) and materials rich in Al (e.g. clays like kaolin, betonies, and burned clays). Because of its availability, fly ash is considered among the important sources of geopolymer. As per IS 3812 (Part II): 2013, fly Ash is defined as pulverized fuel ash extracted from flue gases by any suitable process such as by cyclone separator or electro-static precipitator’. It is a byproduct of thermal power plants which is facing the problems of its disposal. Government of India has taken initiative through ‘Fly Ash Utilization Programme’ to increase utilization of fly ash in concrete, brick, agriculture etc. It is expected that such program will help to meet the reduction of CO2 emission.